Using the area of habitat to assess the extent of protection of India's birds. (24th June 2022) - Warudkar, Ashwin; Goyal, Naman; Kher, Varun; Vinay, K. L.; Chanda, Ritobroto; Bandi, Raja Sekhar; Jenkins, Clinton N.; Robin, V. V.; Pimm, Stuart L.
Abstract: India hosts multiple global biodiversity hotspots while being one of the most populous countries in the world. Here, we examine how well India has protected its avifauna, based on the fraction of their ranges falling within "protected areas." India has protected 5% of its land this way. The issue is whether India has done better than expected in protecting its threatened species. To this end, we assessed 99 Near Threatened, Threatened, and small‐ranged species by estimating their Area of Habitat (AOH). We refined published species ranges using secondary information on elevation limits and habitat preferences. More than half (52) of the species assessed have their AOH <30% of their published ranges, while 31 have <10%. India has protected 87 threatened species' AOH more than expected (>5%), and for 33 species, the proportion protected exceeds the Aichi target (>17%). When we consider the top 10% richest regions as hotspots, only 9.2% of their total area falls under India's protected area network, inadequately covering areas with most threatened birds. We also discuss the conservation concerns for grassland and open habitat species across India, since we find that substantial proportions of their AOHs fall outside protected areas. This result highlights the significance of alternative conservation models, including other effective area‐based conservation measures. We show that species' AOH provides a more realistic well‐informed range that can aid in assessing their protection status. Abstract : With the rapid diminishing of suitable habitats globally, the knowledge of the distribution of biodiversity is inappropriately represented and poses challenges for conservation. We calculated the area of habitat (AOH) for 99 threatened and small‐ranged bird species in India from their published distribution ranges and assessed the spatial extent of their protection. We found that in India, the AOH is substantially smaller than the published range for a majority of the bird species, while most of them have more than 5% of their AOH protected.